Abnormal Uterine Bleeding – A Clinico-pathological Study - ., Sarita; Marla, Nisha J; ., Nagarathna; S, Jayaprakash C (Annals of Pathology and Laboratory Medicine, 2021)
Background: Abnormal Uterine Bleeding (AUB) can occur at any age in a woman`s reproductive period and needs to be assessed very carefully and immediately. When it occurs in the older age group, a more meticulous screening for malignancy is imperative so that treatment can be more radical. Dilatation and curettage is a simple, cost effective, safe and a reliable investigation and it gives us a direct access to the target organ. Methods: Study was conducted prospectively on 162 patients presenting with AUB in reproductive, perimenopausal and postmenopausal age group. All the endometrial samples procured from the endometrial curettage were fixed in 10% buffered formalin for 12-24 hours, processed in the automated tissue processor, cut and stained with Hematoxylin & Eosin (H & E) stain and were finally studied in detail for the morphological findings under light microscopy. Result: In our study Secretory endometrium was most common type, which was followed by Proliferative endometrium. Disordered proliferative endometrium and Endometrial hyperplasia were the commonest histopathological patterns seen in AUB of organic type. Endometrial carcinoma was seen more commonly in postmenopausal age group. Further, in our study Mc Cluggage criteria was applied to all the samples to categorize endometrial samples which were unassessable and inadequate. Conclusion: Evaluation of Endometrial samples is important in all patients with Abnormal Uterine Bleeding (AUB) to find out the Organic Pathology. Histopathological typing of endometrium is crucial for appropriate therapy. Its interpretation is quite challenging and also may show considerable interobserver variability. In AUB, the endometrial samples should be taken during the bleeding episode itself. Dilatation and curettage is a simple, cost effective, safe and reliable investigation and gives us a direct access to the target organ.